Factors Influencing Transactional Leadership in Commercial Banks of Nepal - Karki, Anil; Maharjan, Pushpa (Journal of Business and Social Sciences Research, 2022)
This paper analyses different factors promoting transactional leadership in commercial banks of Nepal. The study is based on primary data with 131 responses. The self-administered questionnaires are used to collect the perceptive opinions from the respondents. The statistical tools used in this study include mean, standard deviation, coefficient of variance and ranking. The study concludes that leaders of commercial banks of Nepal provide subordinates with material and rewards contingent on the fulfilment of contractual obligations, monitored deviation from norms and provide corrective action, frequently implement punishment or corrective approaches are most important factors to transactional leadership styles. Transactional leadership style exists in commercial banks of Nepal.